Quantitative Analysis of Newly Synthesized Proteins - Ma, Yuanhui (Nat Protoc, 2018)
Measuring how proteomes respond to perturbations is crucial to understanding the underlying mechanisms involved. Traditional quantitative proteomic methods are limited by the large numbers of proteins in the proteome and the dynamic range of the mass spectrometer . A previously developed method uses the biorthogonal reagent azidohomoalanine (AHA), an analog of methionine, for labeling, enrichment and detection of newly synthesized proteins (NSPs). Newly synthesized AHA-proteins can be coupled to biotin via CuAAC-mediated click-chemistry and enriched using avidin-based affinity purification. . The combination of AHA-mediated NSP labeling with metabolic stable isotope labeling has subsequently allowed the quantitation of low-abundant, newly secreted proteins by mass spectrometry (MS). However, the resulting multiplicity of labeling complicates the analysis of the newly synthesized proteins. We developed a new NSPs quantification strategy called HILAQ (Heavy Isotope Labeled Azidohomoalanine Quantification) which uses a heavy isotope labeled AHA molecule to enable NSP labeling, enrichment, identification, and quantification. In addition, AHA-peptide enrichment employed in HILAQ improves both the identification and quantification of NSPs over AHA-protein enrichment. Here, we provide a step-by-step description of the HILAQ method that includes procedures for (1) pulse-labeling NSPs and harvesting; (2) addition of biotin by click reaction; (3) protein precipitation; (4) protein digestion; (5) enrichment of AHA-biotin peptides by neutravidin beads and four-step elution; (6) MS analysis; and (7) data analysis for identification and quantification by ProLuCID and pQuant. We demonstrate our HILAQ approach using by identifying NSPs from cell cultures, but we anticipate that it can be adapted for applications in animal models. The whole protocol generally takes six days to complete.